2005
DOI: 10.4028/www.scientific.net/msf.475-479.2037
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of High-Speed Microactuator Utilizing Shape Memory Alloy Thin Films

Abstract: Dynamic actuation properties of two types of high-speed microactuators utilizing Ti-Ni-based thin films were investigated. One type is a microactuator utilizing a Ti-Ni-Pd thin film which has high transformation temperatures. Cooling rate of a microactuator increases with increasing temperature difference between transformation and atmosphere temperatures, thus the increase in transformation temperature is effective to increase the actuation response. The other type is a microactuator using R-phase transformat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 10 publications
0
6
0
Order By: Relevance
“…For high-frequency microactuator applications of SMA thin films a high actuation effect (recovery stress, σ ) is desired as well as high transformation temperatures. The latter enable higher thermal gradients between the thin film actuator and the environment and thus allow for faster cooling rates, hence higher frequencies of operation [28]. Heating of thin film actuators using an electrical pulse is fast compared to the cooling process and thus cooling is the limiting step with respect to the frequency of operation [29].…”
Section: Resultsmentioning
confidence: 99%
“…For high-frequency microactuator applications of SMA thin films a high actuation effect (recovery stress, σ ) is desired as well as high transformation temperatures. The latter enable higher thermal gradients between the thin film actuator and the environment and thus allow for faster cooling rates, hence higher frequencies of operation [28]. Heating of thin film actuators using an electrical pulse is fast compared to the cooling process and thus cooling is the limiting step with respect to the frequency of operation [29].…”
Section: Resultsmentioning
confidence: 99%
“…65 The R-phase transformation shows a very narrow thermal or stress hysteresis, which makes it suitable for applications in microactuators with high working frequency. 66 The working frequency of a thin film using the B199 transformation is limited at 50 Hz, and the displacement decreases with increasing working 5 Comparison of functional fatigue resistance during thermal cycling of three types of NiTi springs associated with R-phase, B19 martensite phase (O) and B199 martensite phase (M) transformation respectively 60 frequency from 0?2 to 50 Hz. 67 However, Tomozawa et al 68 found that the microactuators, which were developed using the R-phase transformation of a thin film, can work at a high frequency up to 125 Hz without losing the working displacement.…”
Section: Unique Properties and Applicationsmentioning
confidence: 99%
“…Thus the actuation speed is limited by the width of thermal transformation hysteresis (Δ T ) and the transformation temperatures. SMA microactuators with a small Δ T 2–9 can be driven at high actuation frequency. SMA microactuators with high transformation temperatures relative to the ambient temperature can also effectively increase the actuation speed by a steeper temperature gradient on cooling.…”
Section: Introductionmentioning
confidence: 99%